Tool wear and surface finish investigation in high speed turning using cermet insert by applying negative rake angles - Adesta, Erry Yulian Triblas; Riza, Muhammad; Al Hazza, Muataz Hazza Faizi; Agusman, Delvis; Yahuza, Rosehan (EuroJournals Publishing, Inc., 2009)

(untitled)
Cermets are not new, in spite of their growing use in recent years. This is due more to the improvement of the cermet grades, improved stability, speeds and conditions as well as the trend towards near-to-finish workpiece blanks. This experiment is to investigate tool wear and surface roughness under different rake angles and different cutting speed. Experiments were carried out by using cermet (CT5015). Different rake angles have been applied in the experiments which are 0, -3. -6, -9 and -12 respectively and cutting speed 1000 m/minute and feed rate 800 mm/minute have been applied. For every single pass of cutting, surface roughness of workpieces were measured by surface roughness tester. The experimental results showed that by increasing negative rake angles the higher wear occurred shorter duration of tool life and poor surface finish. The different between high Tool Wear and Surface Finish Investigation in High Speed Turning Using Cermet Insert by Applying Negative Rake Angles 181 speed and conventional speed was also observed in this experiment. High speed turning gives shorter tool life, high wear rate but finer surface finish than conventional one.